2012
DOI: 10.1167/iovs.12-9813
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Correlation between Hyperpigmentary Changes on Color Fundus Photography and Hyperreflective Foci on SDOCT in Intermediate AMD

Abstract: A novel algorithm achieves automated intermodality spatial coregistration for masked grading of regions selected on CFP and SDOCT. In intermediate AMD, macular hyperpigmentation has high spatial correlation to SDOCT hyperreflective foci and often represents the same anatomical lesion. (ClinicalTrials.gov number, NCT00734487.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
75
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 30 publications
3
75
0
Order By: Relevance
“…14 Hyperreflective foci (HF) were defined as hyperreflective material above the RPE and on the top of drusen. 12 We defined the presence of hyperreflective foci if there were five or more focal hyperreflectivity material in more than one SD-OCT B-scan. Nascent geographic atrophy is defined on SD-OCT by evidence of photoreceptor loss, such as the subsidence of the inner retinal layers (outer plexiform layer and inner plexiform layer) or a hyporeflective wedgeshaped band within the limits of the outer plexiform layer, in a region of RPE disruption and signal hypertransmission at the level of the choroid.…”
Section: Clinical Gradingmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Hyperreflective foci (HF) were defined as hyperreflective material above the RPE and on the top of drusen. 12 We defined the presence of hyperreflective foci if there were five or more focal hyperreflectivity material in more than one SD-OCT B-scan. Nascent geographic atrophy is defined on SD-OCT by evidence of photoreceptor loss, such as the subsidence of the inner retinal layers (outer plexiform layer and inner plexiform layer) or a hyporeflective wedgeshaped band within the limits of the outer plexiform layer, in a region of RPE disruption and signal hypertransmission at the level of the choroid.…”
Section: Clinical Gradingmentioning
confidence: 99%
“…[1][2][3][4][5] These two limitations have started to be addressed with the widespread availability of MMI techniques and the development and manufacture of scotopic perimeters. The advances in MMI with fundus autofluorescence (FAF), near infrared (NIR), and spectral-domain optical coherence tomography (SD-OCT) imaging allowed features, such as SDD, [7][8][9][10] hyperreflective foci, [11][12][13] and nascent geographic atrophy (nGA), 14,15 all of which are considered to be associated with an increased risk of vision loss in AMD, to be identified. Instruments, such as the scotopic Nidek microperimeter (MP-1S; Nidek Technologies, Padova, Italy) 16 and the scotopic Macular Integrity Assessment (S-MAIA; CenterVue, Padova, Italy) microperimeter, 16,17 were designed to allow static rodmediated function to be assessed at multiple locations within the macula in the one testing session.…”
mentioning
confidence: 99%
“…Instead, this study considered HF located within the EZþOS to be (y ¼ 1). The original metric also considered the RNFL, RGCþIPL, and INL combined as (y ¼ 5), instead of the INL only in this study, because no HF were observed in the other layers in our previous study 28 and we sought to avoid the improper automatic identification of blood vessels as HF; all other designations for the calculation agreed. 6 In cases in which layers are missing due to pathologic changes, the location of a HF is defined as first visible layer above the HF.…”
Section: Imaging and Image Analysismentioning
confidence: 99%
“…5 It has been demonstrated that there is a highly specific spatial correlation of HRF with the apex of drusen 6 and/or subretinal drusenoid deposits (SDD) 4 and that HRF overlying drusen are associated with an increased risk of atrophy at that location. 7 The AREDS2 Ancillary SD-OCT Study reported that GA lesions detected at 2 years were significantly correlated with the presence of HRF and with a greater number of HRF at baseline.…”
mentioning
confidence: 99%